Optimization, Characteristics, and Functions of Alkaline Phosphatase From Escherichia coli - Dong, Yachao; Xia, Yandong; Yin, Jie; Zhou, Diao; Sang, Yidan; Yan, Sufeng; Liu, Qingshu; Li, Yaqi; Wang, Leli; Zhao, Ying; Chen, Cang; Huang, Qiuyun; et al. (Frontiers in Microbiology, 2022)
Weaning of piglets could increase the risk of infecting with gram-negative pathogens, which can further bring about a wide array of virulence factors including the endotoxin lipopolysaccharide (LPS). It is in common practice that the use of antibiotics has been restricted in animal husbandry. Alkaline phosphatase (AKP) plays an important role in the detoxification and anti-inflammatory effects of LPS. This study investigated the protective effects of AKP on intestinal epithelial cells during inflammation. Site directed mutagenesis was performed to modulate the AKP activity. The enzyme activity tests showed that the activity of the DelSigD153G-D330N mutants in B. subtilis was nearly 1600 times higher than that of the wild-type AKP. In this study, an in vitro LPS-induced inflammation model using IPEC-J2 cells was established. the mRNA expression of interleukin-(IL-) 6, IL-8 and tumor necrosis factor-α (TNF-α) were extremely significantly down-regulated, and that of ASC amino acid transporter 2(ASCT-2), zonula occludens protein-1 (ZO-1) and occludin-3 (CLDN-3) were significantly up-regulated by the DelSigD153G-D330N mutant compared with LPS treatment. This concludes the anti-inflammatory role of AKP on epithelial membrane and we are hopeful that this research could achieve a sustainable development for the pig industry.